Contractual Liability In Natural Resource Contracts - Kadhim Jawad, Ali; Mohammed Abid, Muthana (Opción, 2019)
The purpose of this paper is to clarify the legal basis for the contractual liability in accordance with the general principles via qualitative comparative research method. As a result, through the research we will have three opinions in jurisprudence, the first opinion is more acceptable and balanced that preserves the sovereignty of the state over its natural resources and at the same time respect the conventions and contractual conditions. In conclusion, one of the most important effects of the breach of contracts is the responsibility of the nodal direction of the party.